Silicon photonics integrated dynamic polarization controller - Wang, Xuyang (2022)
We designed and demonstrated experimentally a silicon photonics integrated dynamic polarization controller. The overall size of the dynamic polarization controller on chip is 2.830 mm × 0.210 mm × 1 mm. The modulation bandwidth is 30 kHz. By using a variable step simulated annealing approach, we achieve a dynamic polarization extinction ratio greater than 25 dB. A numerical simulation method was used to optimize the relevant parameters of the dynamic polarization controller. It is expected that the dynamic polarization controller can be utilized in fiber communication systems or silicon photonics integrated quantum communication systems to minimize the size and decrease the cost further.